An Empirical Analysis of the Prominent Roles of Taxations in the Synchronicity on Boost of Maritime Industry in Singapore - Vu, Duc Cong; Lee, Kihwan; Vu, Hoang Long (International Journal of Economics and Financial Issues, 2016)
This research examines the causal nexuses of the taxations and financial elements in the synchronistic policy that Singapore has applied to radically boost its maritime & offshore fields to develop its economic growths and make Singapore to be a remarkable country in the world in term of ships building volumes, the numbers of ship registries, and the numbers of deadweight in thousands tons arriving at ports nowadays. There are several factors relating to the economic growths and increased numbers of vessels arriving at ports for instant those are the volumes of import & export merchandises, prices of petrochemical and refined oils, services, etc. In this research, it is aimed at decipher the real effectiveness, the interferences, and the prominent roles of corporate tax (TAX) when it is employed together with the domestic credit to private sector (CRE_X1), the real interest rate (RRATE_X2), and the listed stock companies (STOCK_CO) in one synchronous-financial model during the 1980- 2014 period by using the co-integration and vector error correction models for Granger causality tests, and based on the empirical findings, policymakers could find some interesting issues to their developing plans, hopefully. Keywords: Maritime & Offshore Industry, Economic growth, Co-integration, Granger causality tests, Singapore. JEL Classifications: C1; C2